Influência de parâmetros geométricos na avaliação dos mecanismos resistentes de juntas com chave de cisalhamento em ligações viga-pilar: uma abordagem numérica pelo método dos elementos finitos - Andrade, Maykon Vinicius (Universidade Federal de São Carlos, 2025)
In this work, models of beam-column structures were used to examine the behavior of their connections, using a shear-key connection. This connection is commonly used in Brazil in constructions carried out with precast concrete structures. The hypothesis is that with the addition of a grout of concrete welding the beam-column interface with roughness (shear key), the console would be less overloaded and the key would support a part of the load, relieving the console of 100% of the beam load. No numerical studies of this type of connection with steel plates were found, which is why this work is so relevant. For the numerical simulations, the finite element method and the software ABAQUS were used, and ultimately, it was desired, in the end, to determine whether the geometry of the notch of the shear key influences the stress resisted by the corbel and which variable has the greatest influence. The study consisted of 35 simulations, 28 of which involved changes in the beam length and key geometry, and 7 simulations without the key, altering only the beam length for later comparison. Through the numerical simulations, the efficiency of the shear key was verified when compared to the model without the key. It was concluded that the geometry of the key notch, as well as the beam-to-column spacing, are not as significant for resistance, and what truly influences the results is the length of the beam. Finally, the shear key that performed best was the key in the 3.80m long beam, which achieved a relief effect of 58.82% when compared to the model without the key.
Influence of geometric parameters on the evaluation of the resistant mechanisms of shear key joints in beam-column connections: a numerical approach using the finite element method
Keywords: Chave de cisalhamento; Concreto pré-moldado; Estudo numérico; Geometria da chave; Shear-key; Precast concrete; Numerical study; Key geometry; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS